Analysis of Unilateral Termination of Employment Without the Establishment of an Industrial Relations Dispute Resolution Institution in a Force Majeure Situation (Study of Supreme Court Decision Number 374 K/Pdt.Sus-PHI/2023): Analisis Pemutusan Hubungan Kerja Sepihak Tanpa Penetapan Lembaga Penyelesaian Perselisihan Hubungan Industrial dalam Keadaan Force majeure (Studi Putusan Mahkamah Agung Nomor 374 K/Pdt.Sus-PHI/2023) - Arrasyiid, Muhammad Restu; Rasji, Rasji (Indonesian Journal of Law and Economics Review, 2026)
General background: Termination of employment (PHK) in Indonesian labor law requires strict procedural safeguards to protect workers. Specific background: The rise of unilateral PHK during the COVID-19 pandemic, often justified as force majeure, created tensions between substantive justification and mandatory procedural requirements. Knowledge gap: Despite existing regulations, ambiguity persists regarding the legal definition, evidentiary standards, and interaction between force majeure provisions in Article 164(1) and the imperative procedural requirements of Article 151(3). Aims: This study analyzes the legal framework governing PHK due to force majeure and evaluates the validity of termination without formal determination by industrial relations dispute-resolution bodies, focusing on Supreme Court Decision No. 374 K/Pdt.Sus-PHI/2023. Results: Findings show that force majeure lacks a clear legal definition, enabling inconsistent interpretation; the Supreme Court affirmed that termination without procedural determination is null and void, yet still applied reduced compensation under Article 164(1), creating normative inconsistency and insufficient deterrence for employers. Novelty: This research identifies the dual inconsistency between procedural imperatives and substantive relief for employers, proposing a reconstructed normative framework. Implications: Clear statutory definitions, stricter evidentiary standards, and alignment between procedural compliance and compensation rules are required to strengthen worker protection and prevent misuse of force majeure claims. Highlights: Termination of employment without a determination from the industrial dispute settlement body is null and void pursuant to Article 151(3). Force majeure is recognized but lacks a clear legal definition and standardized evidentiary requirements. Supreme Court Decision 374/2023 reveals an inconsistency between procedural violations and the reduced compensation granted. Keywords: Force Majeure, Employment Termination, Industrial Relations, Legal Procedure, Worker Protection